2000
DOI: 10.1016/s0194-5998(00)70233-6
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular autorotation testing in patients with benign paroxysmal positional vertigo

Abstract: A normal horizontal gain or vertical phase lead on vestibular autorotation testing in a vertiginous patient is suggestive of but not exclusive to a diagnosis of BPPV. The combination of a normal horizontal gain and vertical phase lead on vestibular autorotation testing is highly suggestive of the diagnosis of BPPV. Adjuvant use of these parameters in vestibular autorotation testing may prove to be helpful in the diagnosis of BPPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…When the head is placed in a provoking position, the otoconia move in the canal and displace the cupula. This results in vertigo and rotary nystagmus towards the affected ear (Belafsky et al, 2000;Macias et al, 2000). The nystagmus typically lasts for less than one minute and is fatigable after multiple positionings (Lanska & Remler, 1997;Konrad et al, 1999;Belafsky et al, 2000).…”
Section: Sumariomentioning
confidence: 99%
See 1 more Smart Citation
“…When the head is placed in a provoking position, the otoconia move in the canal and displace the cupula. This results in vertigo and rotary nystagmus towards the affected ear (Belafsky et al, 2000;Macias et al, 2000). The nystagmus typically lasts for less than one minute and is fatigable after multiple positionings (Lanska & Remler, 1997;Konrad et al, 1999;Belafsky et al, 2000).…”
Section: Sumariomentioning
confidence: 99%
“…This results in vertigo and rotary nystagmus towards the affected ear (Belafsky et al, 2000;Macias et al, 2000). The nystagmus typically lasts for less than one minute and is fatigable after multiple positionings (Lanska & Remler, 1997;Konrad et al, 1999;Belafsky et al, 2000). Although all three semicircular canals may be affected, posterior canal BPPV is the most common form due to the anatomical position of this canal in relation to the utricle (Herdman & Tusa, 1996).…”
Section: Sumariomentioning
confidence: 99%
“…It has been used to demonstrate abnormalities of the VOR (decreased gain and increased phase) at higher frequencies (which are more related to common daily activities) that were not apparent form conventional vestibular tests: in Ménière's patients [50,51], in panic-disorder patients [52], in patients with various peripheral vestibular disorders [53], and in postoperative vestibular schwannoma patients [54]. In patients with benign paroxysmal positional vertigo, a combination of normal horizontal gain and vertical phase lead on VAT was demonstrated [55] and is suggested to be a diagnostic finding. Hirvonen et al [56] compared two versions of the VAT.…”
Section: Vestibular Autoratational Testmentioning
confidence: 98%
“…Four articles were retrieved and the articles which mentioned that "Dix Hallpike maneuver is the gold standard for diagnosing BPPV" were selected. 6 The authors concluded that "A normal horizontal gain or vertical phase lead on vestibular autorotation testing in a vertiginous patient is suggestive of but not exclusive to a diagnosis of BPPV." Adjuvant use of these parameters in vestibular autorotation testing may prove to be helpful in the diagnosis of BPPV.…”
Section: First Scenariomentioning
confidence: 99%
“…The sensitivity of the combination of normal horizontal gain and vertical phase lead on vestibular autorotation testing is 87% specific but only 25% sensitive in the diagnosis of BPPV. 6 The time taken to retrieve and scan this information was 3 minutes excluding the time taken to critically appraise the article. Dix Hallpike test was performed on the patient, the patient was then seated, Frenzels glasses were used, the neck was extended and turned to one side, and the patient was then rapidly placed supine with her head hanging over the edge of the bed.…”
Section: First Scenariomentioning
confidence: 99%